Water Uptake by Artemisia ordosica Roots at Different Topographic Positions in an Alpine Desert Dune on the Northeastern Qinghai–Tibet Plateau - Wang, Haijiao; Tian, Lihui; Zhang, Hongwei; Yu, Yang; Wu, Huawu (Frontiers in Earth Science, 2022)
Different strategies of water uptake by roots in a semiarid desert are one way that plants adapt to the water-limited environment. In this study, stable isotopes of δ18O were used to analyze the variability in water sources of the native species Artemisia ordosica during the growing season in an alpine semiarid desert on the Qinghai–Tibet Plateau, China. A. ordosica depended primarily on water from upper soil layers in the early growing season, except for those windward, which obtained water from three soil layers as well as groundwater from 0.19 to 0.28. In the summer, A. ordosica switched sources, and those individuals at the top of the dune used 0.85 of water from middle soil layers, whereas those on windward (0.27 to 0.33) and leeward (0.31 to 0.37) slopes absorbed water from three soil layers. Shallow soil water was the main water source at all sites at the end of the growing season. The water uptake pattern of A. ordosica was consistent with the root distribution in positions with different dune geomorphology. The results suggest that the microlandforms of sand dunes affect vegetation growth not only through aeolian activities and soil properties but also through plant water use.